2011
DOI: 10.3748/wjg.v17.i3.322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heme oxygenase-1 on renal function in rats with liver cirrhosis

Abstract: Low HO-1 expression level in kidney is an important factor for experimental HRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 28 publications
2
24
1
Order By: Relevance
“…Prior to the pharmacokinetic experiments, the animals were fasted for 12 h with water available ad libitum. Biliary cirrhosis with PH was induced via bile duct ligation (BDL) as previously described (12). The surgical procedures were approved by the Animal Care and Use Committee of Dalian Medical University.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the pharmacokinetic experiments, the animals were fasted for 12 h with water available ad libitum. Biliary cirrhosis with PH was induced via bile duct ligation (BDL) as previously described (12). The surgical procedures were approved by the Animal Care and Use Committee of Dalian Medical University.…”
Section: Methodsmentioning
confidence: 99%
“…Protein concentration was determined according to the Lowry method using bovine serum albumin as a standard. The western blot assay was performed as previously described (12). Total protein (20 µg/ml) was separated by 10% sodium dodecyl sulphate-polyacrylamide gel electrophoresis and transferred to a polyvinylidene difluoride membrane (EMD Millipore, Bedford, MA, USA).…”
Section: Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain biopsies are rarely performed in patients with HE due to the temporary nature of the disease and surgery often not being necessary; therefore, the animal experiment provides an appropriate supplement to the cerebral pathology of patients with HE. In addition, we demonstrated that HO-1 is important in a number of organs involved in end-stage liver disease (9,10). Thus, additional research with selective HO inhibitors and their doses is required.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have indicated that HO-1 expression is upregulated in the liver and the HO/CO pathway may regulate cirrhosis induced in rats by bile duct ligation (BDL), as well as its complications, including hepatorenal and hepatopulmonary syndrome (9,10). In addition, the levels of carboxyhemoglobin (COHb) in the arterial blood of hepatitis B virus-related cirrhosis patients with HE were significantly increased compared with healthy individuals (11).…”
Section: Introductionmentioning
confidence: 99%